Nauczanie języka przez literaturę, a literatury przez język - o metodzie skorelowanej w pracy z uczniami polonijnymi = To language through literature, to literature through language - about the correlated method in teaching heritage language learners - Lipińska, Ewa; Seretny, Anna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The heritage language and the mother tongue as school subjects are not the same. Therefore, they require a different approach; namely, in the case of teaching the heritage language, it is necessary to focus more on the language itself than on the historical and literary education of pupils.
Keywords: nauczanie języka odziedziczonego; tekst literacki; metoda skorelowana; integracja kompetencji językowych; heritage language teaching; literary text; correlated method; integrated skill development scheme